Sharing the Ride: Ixodes scapularis Symbionts and Their Interactions - Stewart, Philip E.; Bloom, Marshall E. (Frontiers in Cellular and Infection Microbiology, 2020)
The deer tick Ixodes scapularis is the leading vector of disease agents in the United States, spreading the bacteria that causes Lyme disease, protozoan agents of babesiosis, and viruses such as Powassan. However, a variety of other organisms have also evolved symbiotic relationships with this tick species, and it seems likely that some of these microbes have simultaneously coevolved mechanisms to impact each other and their eukaryotic host. The number of organisms identified as I. scapularis symbionts has increased seemingly exponentially with the advent of PCR and next generation sequencing technologies, but convincing arguments have proposed that many of these are either inadvertently acquired and do not persist long-term or that they are artifacts of ultrasensitive detection methods. In this review, we examine the merits of whether these organisms are true symbionts of I. scapularis, and the evidence for interactions occurring within the “scapulome”.